Peran Dosen Native Speaker dalam Pembelajaran Bahasa Arab di Perguruan Tinggi - Taflilah, Dina; Nordin, Puan Farah Nadiah (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2024)
This study aims to analyze the implementation of Arabic language learning with a native speaker at the Arabic Language Education Program (PBA) of UIN Walisongo Semarang, the role of the native speaker in enhancing language skills, and the responses of the 2021 cohort students to their presence. Employing a mixed methods approach with a convergent parallel design, the study integrates qualitative data from observations, interviews, and documentation, and quantitative data from a Guttman scale questionnaire involving 24 International Class Program (ICP) students in the sixth semester. Findings indicate that the native speaker enhances kalām (speaking) and istimāʿ (listening) skills through a bī’ah lughawīyah (Arabic language environment). The native speaker serves as a teacher, authentic language source, motivator, facilitator, and provider of Arabic cultural insights. Students responded positively, most agreeing on the native speaker’s role and expressing satisfaction and comfort. The study suggests integrating native and non-native teachers and developing cultural modules for optimal learning outcomes.